Keuntungan Usaha Ternak Sapi Bali dan Pertumbuhan Ekonomi Sektor Pertanian di Sentra Pengembangan Kabupaten Konawe Selatan - Gerhana Gerhana; Wiwiek Rindayati; Dominicus Savio Priyarsono (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The economic growth of the agricultural sector, particularly the Bali cattle farming subsector, plays a significant role in improving both regional and farmer-level economies, as evidenced by the profits gained from cattle farming. This study aims to analyze the profitability of Bali cattle farming and assess the economic growth of the agricultural sector in the Bali cattle development centers of South Konawe Regency. The research was conducted from June to August 2024. The study location was determined using purposive sampling, focusing on the South Konawe Regency in four priority subdistricts for Bali cattle development: Baito, Palangga, Buke, and Tinanggea, with 120 Bali cattle farmers as respondents. Primary data were collected directly from farmers through questionnaires and Focus Group Discussions (FGDs) involving local government officials, livestock extension workers, Bali cattle farmers, and academics. The primary data variables include farmer characteristics and production factors in Bali cattle farming, encompassing the inputs and outputs used. Secondary data were obtained from the Central Bureau of Statistics (BPS), the Department of Livestock and Animal Health (PKH), agricultural extension offices (BPP), the Regional Development Planning Agency (DDP), and other relevant sources. The Policy Analysis Matrix (PAM) was used to analyze the profitability of Bali cattle farming, while economic growth in the agricultural sector was assessed using Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift Share (SS), and Klassen Typology (KTK) analyses. The PAM analysis results indicate that Bali cattle farming yields a private profit of IDR 1,614,465 per head per year and a social profit of IDR 6,806,079 per year, demonstrating efficiency and viability. The LQ, DLQ, and SS analysis results reveal that the agricultural sector exhibits economic growth with an LQ value of 1.03, DLQ value of 1.17, and SS values (Rij 0.16, Ri 0.16, Ra 0.16, PBij 332.76, PNij 341.70, PPij 15.10, PPWij 6.16). These findings indicate that the sector is a competitive, prospective, and leading base sector, although its growth is relatively slow. Therefore, the government is encouraged to pay attention to and support future policies by considering the contribution of agricultural sector growth and assisting Bali cattle farmers in maintaining profitability in their farming activities.